Synthesis and gas transport properties of novel poly(aryl ether ketone)s with branched structure. Issue 4 (19th July 2013) - Gao, Cong; Li, Xiujie; Jiang, Zhenhua; Wei, Wei; Wang, Guibin; Zhang, Shuling
<x xml:space="preserve">Abstract</x> Poly(aryl ether ketone) membranes with enhanced gas permeability and selectivity were prepared by the incorporation of the branched structure. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>